Molecular epidemiology of Pseudomonas aeruginosa clinical isolates from Portuguese Central Hospital - Fonseca, A P; Correia, P; Extremina, C I; Sousa, J C; Tenreiro, R; Barros, H (Folia microbiologica, 2008)
The relatedness between clinical isolates of P. aeruginosa obtained from patients during their stay in a Portuguese Central Hospital was evaluated. Genotypic fingerprinting (M13-PCR), phenotypic methods (biotyping and antibiotyping) and epidemiological information (spatial and temporal links) were used to evaluate the relatedness between 88 clinical isolates (68 patients), selected randomly out of 189. Sixty-two M13 types were found, 12 of them containing isolates from more than one patient. Thirty-four antibiotypes were found, as well as a significant association (p < 0.05) between epidemic isolates and multiresistance patterns. The nosocomial transmission of P. aeruginosa strains may be limited since M13 typing demonstrated a high degree of diversity among all the isolates, suggesting the occurrence of mainly independent infectious episodes. The results show the possible occurrence of cross-acquisition, cross-colonization and cross-infection and suggest an epidemic population structure for P. aeruginosa in this hospital.
Keywords: infekce spojené se zdravotní péčí; Polymerase Chain Reaction; polymerázová řetězová reakce; Electrophoresis, Gel, Pulsed-Field; pseudomonádové infekce; genotyp; Sampling Studies; Humans; vzorkové studie; DNA bakterií; DNA, Bacterial; Portugalsko; Cross Infection; pulzní gelová elektroforéza; Pseudomonas aeruginosa; Drug Resistance, Microbial; nemocnice fakultní; Pseudomonas Infections; antibiotická rezistence; lidé; Genotype; Portugal; Hospitals, Teaching